DEVELOPMENT OF LEADERSHIP CULTURE FOR SUSTAINABILITY: A SYSTEMATIC LITERATURE REVIEW - Yunia Wardi; Fitra Mulya; Rino (SOSIOEDUKASI, 2025)
This study aims to explore how leadership culture oriented towards sustainability can be implemented across various organizations. Using a Systematic Literature Review (SLR) approach with the PRISMA 2020 guidelines, this research examines articles discussing various leadership models that support sustainability, including CSR leadership, transformational leadership, collaborative leadership, and experience-based leadership. Out of 155 articles found, 9 articles that met the inclusion criteria were analyzed to uncover their contribution to the development of a leadership culture that supports sustainability goals. The main findings show that CSR leadership, which integrates sustainability into organizational strategy, can enhance organizational learning and the adoption of green technologies. Additionally, transformational and collaborative leadership have proven effective in motivating employees and strengthening organizational commitment to long-term goals. This study also highlights the importance of gender equality in leadership, which can accelerate organizational sustainability. In conclusion, various inclusive, CSR-based, and transformational leadership models are highly relevant in supporting a sustainability culture in organizations. This research contributes to the understanding of how organizations can develop more sustainable leadership.